Antibiotic resistance in Campylobacter: emergence, transmission and persistence. (March 2009) - Luangtongkum, Taradon; Jeon, Byeonghwa; Han, Jing; Plummer, Paul; Logue, Catherine M; Zhang, Qijing
Campylobacter is a leading foodborne bacterial pathogen, which causes gastroenteritis in humans. This pathogenic organism is increasingly resistant to antibiotics, especially fluoroquinolones and macrolides, which are the most frequently used antimicrobials for the treatment of campylobacteriosis when clinical therapy is warranted. As a zoonotic pathogen, Campylobacter has a broad animal reservoir and infects humans via contaminated food, water or milk. Antibiotic usage in both animal agriculture and human medicine, can influence the development of antibiotic-resistant Campylobacter . This review will describe the trend in fluoroquinolone and macrolide resistance in Campylobacter, summarize the mechanisms underlying the resistance to various antibiotics and discuss the unique features associated with the emergence, transmission and persistence of antibiotic-resistant Campylobacter . Special attention will be given to recent findings and emphasis will be placed on Campylobacter resistance to fluoroquinolones and macrolides. A future perspective on antibiotic resistance and potential approaches for the control of antibiotic-resistant Campylobacter, will also be discussed.